Nekatere značilnosti doživljanja sebe pri osebah s shizofrenijo in pri tistih po nezgodni poškodbi hrbtenjače - Horvat, Barbara (Psihološka obzorja (Ljubljana), 2013)
Self-experiencing is synonymous with the phrase who am I. Each of us expresses his compliance with social norms and social environment through it. It takes place in different areas of a persons life and in conjunction with different social roles. The sense of continuity throughout the different periods of life is very important. Stressful events, also difficult injuries and diseases, upset and change the experience of oneself. Schizophrenia and spinal cord injuries can be classified in this category. The results of various studies suggest that in people with schizophrenia diffuse identity is present; in subjects after spinal-cord injury the physical disability is crucial and importantly affects the physical self-image. The main problem of our study was to compare the characteristics of self-experience in people with schizophrenia and those after spinal cord injury. We assumed significant differences in self-experience on different subscales (mainly in the field of social and physical self concept) between the two comparison groups. 90 participants were involved in the study, 30 in each group (people with schizophrenia, people after spinal cord injury and a control group of people without any present signs of pathology). We applied the Tennessee self-concept scale and the semantic differential assessment of Self. The results showed general low (or even negative) self evaluations in the group of people with schizophrenia, while in the group of people after spinal-cord injury idealization was present. This group of people is under a great influence of defensive mechanisms, which allow the validation of a positive self concept. Important derogations were also shown on some subscales. We believe that the results of the study are especially important in the psychological work with representatives of the two populations. People with schizophrenia should be introduced with the meaning of self-experiencing in different areas, while people after spinal cord injury should be taught how to replace defensive mechanisms with constructive coping strategies which help to experience ourselves objectively.
Keywords: doživljanje sebe; Self Concept; samopodoba; Schizophrenia; shizofrenija; Spinal Cord Injuries; Slovenia; nezgodne poškodbe hrbtenjače; self-experience; Tennesseejska lestvica koncepta sebe TSCS-2; Tennessee self-concept scale TSCS-2